The joint role of systemic immune-inflammation index and geriatric nutritional risk index in cancer survivors and their impact on all-cause mortality - Chen, Xiangrui; Hu, Min; Hao, Chengluo; Li, Jun; Han, Yunwei (Frontiers in Nutrition, 2025)
IntroductionThis study aimed to investigate the combined predictive value of the Systemic Immune-Inflammation Index (SII) and the Geriatric Nutritional Risk Index (GNRI) for all-cause mortality in cancer survivors.MethodsUsing NHANES data (1999–2018), 2,969 eligible cancer survivors were categorized into four groups based on SII and GNRI levels. Mortality risk was assessed through unadjusted and fully adjusted Cox proportional hazards models.ResultsThe combination of low SII and high GNRI was associated with the lowest mortality risk (HR = 1.0, reference). In contrast, high SII and low GNRI significantly increased mortality risk (fully adjusted HR = 6.178, 95% CI: 2.669–14.299). Both unadjusted and adjusted models confirmed that high SII correlated with higher mortality, while low GNRI independently predicted poorer outcomes. Subgroup analyses revealed significant interactions between the SII-GNRI combination and gender/alcohol consumption.DiscussionThe findings highlight SII and GNRI as critical predictors of all-cause mortality in cancer survivors. Their combined assessment may improve risk stratification and guide targeted clinical interventions.